Chapter 9 ‘Putting the Fun Back into Fundamentalism’ - Abdel-Fadil, Mona (Bristol University Press, 2022)
EPDF of Chapter 9 available Open Access under CC-BY-NC-ND licence.This thought-provoking collection takes a multi-disciplinary approach to the subject of humour in Islam. It ranges across sociological, cultural, theological and political themes, presenting examples of comedy in both Muslim and non-Muslim countries. The book also investigates humour’s role in fundamentalism, addresses sensitive contexts of freedom of speech and blasphemy, and corrects common misunderstandings about laughter in Islam.